Response of herbaceous species to a degradation gradient in the western region of Etosha National Park, Namibia - W.P. Du plessis; G.J. Bredenkamp; W.S.W. Trollope (Koedoe: African Protected Area Conservation and Science, 1998)
The degradation status of 88 sample plots situated in two plant communities in the western region of Etosha National Park was determined. Herbaceous species frequency was correlated by means of an ordination technique with utilisation intensities. Species were categorised in ecological categories (Decreasers and Increasers) according to their abundance along a degradation gradient. This more objective approach is compared with an initial subjective grouping of species. The dangers of blindly following the ordinated results are discussed, and it is concluded that ordination results need to be verified by careful ecological interpretation.